A waterproof, environment‐friendly, multifunctional, and stretchable thermoelectric fabric for continuous self‐powered personal health signal collection at high humidity - Xinyang He; Bingyi Li; Jiaxin Cai; Honghua Zhang; Chengzu Li; Xinxin Li; Jianyong Yu; Liming Wang; Xiaohong Qin (SusMat, 2023)
Abstract Thermoelectric sensors have attracted increasing attention in smart wearables due to the recognition of multiple signals in self‐powered mode. However, present thermoelectric devices show disadvantages of low durability, weak wearability, and complex preparation processes and are susceptible to moisture in the microenvironment of the human body, which hinders their further application in wearable electronics. Herein, we prepared a new thermoelectric fabric with thermoplastic polyurethane/carbon nanotubes (TPU/CNTs) by combining vacuum filtration and electrospraying techniques. Electrospraying TPU microsphere coating with good biocompatibility and environmental friendliness made the fabric worn directly and exhibits preferred water resistance, mechanical durability, and stability even after being bent 4000 times, stretched 1000 times, and washed 1000 times. Moreover, this fabric showed a Seebeck coefficient of 49 μV K−1 and strain range of 250% and could collect signals well and avoided interference from moisture. Based on the biocompatibility and safety of the fabric, it can be fabricated into devices and mounted on the human face and elbow for long‐term and continuous collection of data on the body's motion and breathing simultaneously to provide collaborative support information. This thermoelectric fabric‐based sensor will show great potential in advanced smart wearables for health monitoring, motion detection, and human–computer interaction.